Estimasi Cadangan Karbon dan Serapan Karbondioksida Biomassa Tegakan Mangrove di Gunung Anyar, Surabaya - Dandy Aditya Permana; Nirmalasari Idha Wijaya; Mahmiah (Universitas Hang Tuah, 2022)
Mangrove forests are forests that are able to store carbon and absorb carbon dioxide with the best ability compared to other forests. This study aims to analyze the condition of the mangrove forest and to analyze the estimation of carbon stock and carbon dioxide uptake from tree stands and saplings in the Gunung Anyar mangrove forest. The main data needed in this research is the number of individuals and the amount of biomass of mangrove stands. The research method used is the survey method. Determination of the location and sampling technique was carried out by purposive sampling with 3 transect lines (Transect Line Plot). Estimation of carbon stock and carbon dioxide uptake was done by non-destructive method and allometric equation approach. The condition of the Gunung Anyar mangrove forest for tree stands was damaged, while the saplings were good, the dominant type of mangrove was Avicennia marina. The estimated carbon stocks of tree stands and saplings were 38.67 tons C/ha and 9.26 tons C/ha, respectively. The carbon absorption of tree stands and saplings was 71.25 tons CO2/ha and 34.99 tons CO2/ha.